2019
DOI: 10.1177/1120700018823504
|View full text |Cite
|
Sign up to set email alerts
|

It is safe to use minimal restrictions following posterior approach total hip arthroplasty: results from a large cohort study

Abstract: Background: To prevent early postoperative dislocation following a total hip arthroplasty (THA) procedure, patients must adhere to restrictions. Restrictive protocols are common if THA surgery is performed using the posterior approach, but scientific evidence form larger studies that supports these restrictions are scarce. In this large cohort study we compare the <90-days dislocation rate between patients receiving posterior approach THA managed with minimal versus extensive restrictions. Methods: Prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Traditionally, it had been recommended to have restricted mobilization following THAs to reduce the risk of dislocation and muscle detachment, including the use of an abduction pillow, particularly for patients that had a posterior approach. It has become clear that these post-operative restrictions are unnecessary and not supported by peer-reviewed publications; as the hospital stay has shortened, these restrictions have been reduced and there has been no increase in cases of early THA instability (35,75). In addition, van der Weegen et al performed a prospective consecutive series of 1,049 primary THAs managed with minimal post-operative restrictions and compared the rate of instability to a prior consecutive series of cases from the same institution using a posterior approach and a traditional restrictive protocol; they found an instability rate of 1.6% in the minimal restrictive groups as compared to 2.5% in the traditional restrictive group, and they concluded that patients can be managed safely with minimal restrictions following posterior approach THA (75).…”
Section: Treatment Options For Dislocation Following Thamentioning
confidence: 99%
“…Traditionally, it had been recommended to have restricted mobilization following THAs to reduce the risk of dislocation and muscle detachment, including the use of an abduction pillow, particularly for patients that had a posterior approach. It has become clear that these post-operative restrictions are unnecessary and not supported by peer-reviewed publications; as the hospital stay has shortened, these restrictions have been reduced and there has been no increase in cases of early THA instability (35,75). In addition, van der Weegen et al performed a prospective consecutive series of 1,049 primary THAs managed with minimal post-operative restrictions and compared the rate of instability to a prior consecutive series of cases from the same institution using a posterior approach and a traditional restrictive protocol; they found an instability rate of 1.6% in the minimal restrictive groups as compared to 2.5% in the traditional restrictive group, and they concluded that patients can be managed safely with minimal restrictions following posterior approach THA (75).…”
Section: Treatment Options For Dislocation Following Thamentioning
confidence: 99%
“…9 A large cohort study by Van der Weegen et al, included more than 2000 primary THAs performed with a posterolateral approach, found minimal restrictions was not inferior to usual restrictions in dislocation rates, however, more hips had a femoral head larger than 32 mm in minimal restrictions group. 7 In this study, there was no dislocation in all primary THA, while two (16.7%) dislocations in revision THA with conventional hip precautions. One of the reasons for a low dislocation rate is because of the use of a large femoral head, 62% and 72% of THA have 36 mm femoral head in the MP and CP group respectively.…”
Section: Discussionmentioning
confidence: 47%
“…Traditionally, standard hip precautions avoid placing the hip in at-risk position, aims to nurture soft-tissue healing during the early postoperative phase to reduce the risk of dislocations. However, recent studies showed that more relaxed or minimal restrictions after posterolateral approach THAs did not increase the rate of dislocation, [6][7][8][9] while the use of hip precautions slow down the pace of functional recovery and reduce patient's satisfaction. [10][11][12] There are only several studies specifically examining hip precautions in posterolateral approach THA, [6][7][8][9][10] and even fewer exploring patient's function and quality of with different degrees of restrictions after THA.…”
Section: Introductionmentioning
confidence: 99%
“…The overall rate of dislocation has been recorded to be around 4e8% 4e7 using posterior approach with maximum occurrence in the first 6 weeks as reported by Cobb et al 8 Posterior approach has been associated with dislocation to such an extent that many surgeons also restrict their patients in doing a lot of activities (squatting, sitting on floor, adduction of hips) following THA with this approach. However, Van der Weegen et al 9 in 2019 in their prospective cohort study reported how minimal restrictions with large femoral head were as safe as extensive restrictions to prevent dislocations when THA's were performed by the posterior approach. Miller et al 10 in their systematic review of 1,67,308 THA's done by direct anterior and posterior approach reported higher dislocation and reoperation rates in the posterior approach.…”
Section: Discussionmentioning
confidence: 99%